Reading Homer's Iliad - Myrsiades, Kostas 1941- (Bucknell University Press, 2023)
"We still read Homer's epic The Iliad two-and-one-half millennia since its emergence for the questions it poses and the answers it provides for our age, as viable today as they were in Homer's own times. What is worth dying for? What is the meaning of honor and fame? What are the consequences of intense emotion and violence? What does recognition of one's mortality teach? We also turn to Homer's Iliad in the twenty-first century for the poet's preoccupation with the essence of human life. His emphasis on human understanding of mortality, his celebration of the human mind, and his focus on human striving after consciousness and identity has led audiences to this epic generation after generation. This study is a book-by-book commentary on the epic's 24 parts, meant to inform students new to the work. Endnotes clarify and elaborate on myths that Homer leaves unfinished, explain terms and phrases, and provide background information. The volume concludes with a general bibliography of work on the Iliad, in addition to bibliographies accompanying each book's commentary"--